Study of 16O(12C, α20Ne)α for the investigation of carbon-carbon fusion reaction via the Trojan Horse Method. (April 2016) - Rapisarda, G.G.; Spitaleri, C; Bordeanu, C.; Hons, Z.; Kiss, G.G.; La Cognata, M.; Mrazek, J.; Nita, C.; Pantelica, D.; Petrascu, H.; Pizzone, R.G.; Romano, S.; et al.
Abstract: Carbon-carbon fusion reaction represents a nuclear process of great interest in astrophysics, since the carbon burning is connected with the third phase of massive stars (M > 8 M☉ ) evolution. In spite of several experimental works, carbon-carbon cross section has been measured at energy still above the Gamow window moreover data at low energy present big uncertainty. In this paper we report the results about the study of the 16 O( 12 C, α 20 Ne) α reaction as a possible three-body process to investigate 12 C( 12 C, α ) 20 Ne at astrophysical energy via Trojan Horse Method (THM). This study represents the first step of a program of experiments aimed to measure the 12 C+ 12 C cross section at astrophysical energy using the THM.